TINGKAT KEPUASAN PASIEN TERHADAP PELAYANAN KESEHATAN DI PUSKESMAS BAWAN KECAMATAN AMPEK NAGARI KABUPATEN AGAM - Oktafioni, Yuliazmi; Kadarisman, Yoskar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
The health center is one of the health facilities as priority and the yardstick of health, theparticipation of the people, and it his the first comprehensive service of a borough. The pleasureis the feeling some one after a performance or compare results according to feel hope. By thepresence of some patients who said it was satiesfied with health services at Bawan health center,then here is researchers interested for research into Bawan health center with one of the problemswhich are what was the level of satisfaction patients to the public at Bawan health center AmpekNagari sub district Agam district ? For the purpose of knowing how the level of satisfactionpatients against the provision of services by health center workers Bawan. The theory used is thetheory of satisfaction and services. Is the act of services or deed that can be insesible by oneparty to another and was in nature are invisible, palpable, and owned, but limited only to be used,perceived, bough, or rented. A method that is used is descriptive quantitative, that therespondents were selected in the way anyone who accidentally met with researchers and inaccordance with characteristics that researchers set then the person can be used as respondents.Data collections techniques that we use is observation and interview. The accumulated dataanalyzed, mixed with SPSS, and used as table, then given the description of the adverb orcomprehensible and understood by common form of responses from respondents of the objectbecome the focus of research. That whould give a little conclusion. The result of research showsthat of respondents who researchers get 25, negative perception of respondent said or notsatisfied with services at Bawan health center is as much as 20 percent of respondents (80,0 %),they said was not satisfied because the services they receive not in accordance with which theyexpect, as often waited, not served by fast, lack of friendliness, scolds say hello to what patientswith very low against the elderly patients, from the completeness of a medical instrumentpatients also feel less satisfied because they often get referrals due to limited medical devicesthat were in the health centers.Keyword : the level of satisfaction, health services and health center